Enhancing High School Students’ Critical Thinking through HOTS-Based Interactive E-Modules - Baiq Riska Bayu; Baiq Rofina Arvy; Ahmad Nasrullah (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Critical thinking skills are a core competency in mathematics learning, particularly in addressing problems that require higher-level reasoning. However, empirical evidence indicates that students’ critical thinking skills remain relatively low, resulting in limited ability to analyze, evaluate, and draw conclusions when solving complex mathematical problems. This study aimed to examine the effect of using Higher-Order Thinking Skills (HOTS)-based interactive e-modules on students’ critical thinking skills in mathematics learning. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design. The participants consisted of 31 tenth-grade students selected through a saturated sampling technique. The research instruments included observation sheets and a critical thinking skills test, both of which were validated by experts and met reliability criteria. Data were collected through the administration of pretests and posttests and analyzed using a paired-sample t-test to determine differences in students’ critical thinking skills before and after the intervention. The results indicate that students’ critical thinking skills prior to the implementation of the HOTS-based interactive e-modules were relatively low. Following the intervention, students’ critical thinking skills showed a significant improvement, as evidenced by higher posttest scores compared to pretest scores and a statistically significant paired-sample t-test result (p < 0.05). These findings demonstrate that HOTS-based interactive e-modules have a significant positive effect on improving students’ critical thinking skills in mathematics learning. Therefore, the use of HOTS-based interactive e-modules is recommended as an alternative instructional resource to support the development of students’ higher-order thinking skills.